LEGAL CONSEQUENCES FOR ACTORS DOWNLOADING ILLEGAL FREE SONGS VIA INTERNET - Ananza, Almira Sari; Santoso, Budi (Universitas Muhammadiyah Ponorogo, 2023)
Today, internet technology has developed rapidly, which can bring both positive and negative impacts. This study aims to answer the legal consequences that will catch the perpetrators of illegal song downloaders through the internet. This research is included in the type of normative research with a literature study approach and legislation related to copyright. The study results show that creators and copyright holders are given legal protection for their inspiration and creativity. Legal consequences for copyright violators for downloading songs illegally on internet media can be subject to civil and criminal sanctions. Based on Articles 96 and 99 of the Copyright Law, the creator or copyright holder is entitled to civil compensation for infringement of his work and the loss of economic rights. Criminally, violators may be subject to sanctions through imprisonment and fines.